Linguistic Landscape in Braga Street, Bandung: Multilingual Practices and Cultural Identity - Mubarok, Yasir; Kurniawan, Muhammad Ardian; Nurhuda, Zamzam; Risnawati, Eris (Insaniyat: Journal of Islam and Humanities, 2025)
This study investigates the linguistic landscape of Jalan Braga, Bandung, a heritage street rich in historical and cultural significance. Using a qualitative descriptive design, data were collected through photographic documentation, field observation, and secondary sources, resulting in 60 signage items analyzed. Findings reveal that monolingual signage dominates (68.3%), particularly in English and Indonesian, followed by bilingual (23.3%) and multilingual signs (8.4%). The results demonstrate that English functions both as a global lingua franca and a branding tool, while Indonesian serves as a marker of national identity. Dutch signage symbolizes colonial heritage, whereas Sundanese, though limited in number, reflects local cultural identity. Multilingual signs, though fewer, strategically integrate languages such as Japanese, Korean, and Mandarin to project cosmopolitanism and cultural hybridity. The study highlights how language use in Braga reflects not only practical communication but also symbolic functions tied to identity, history, and globalization. This research contributes to linguistic landscape studies by emphasizing the interplay of colonial, national, local, and global languages in urban heritage spaces.